FinTech as a Lever for the Digital Economy: Between Growth and Challenges – An Analytical Approach - Kerdouci, Marwa; Meghdour, Fatima Zahra; Guerrouf, Salah (Journal of Ecohumanism, 2025)
This study aims to shed light on the growing role of financial technology (FinTech) as a key lever of the digital economy, through an analysis of the current state of global investments in this sector, as well as an examination of usage trends and the expansion of FinTech start-ups. The analysis is based on international reports, academic studies, and recent applied experiences. The findings indicate that, despite the decline in FinTech investments in 2022 due to economic pressures and geopolitical crises, the sector continues to maintain its position as one of the most important areas of digital finance. Notably, emerging segments such as digital payments and regulatory technology (RegTech) have gained prominence, while other segments, including insurance technology and cryptocurrencies, have experienced a relative downturn. The study also highlights that start-ups constitute a major driving force behind this transformation, with the United States, China, and the United Kingdom leading the global landscape in terms of the number of companies and investment volumes. Furthermore, projections suggest that the number of FinTech users is expected to exceed seven billion by 2027, reflecting the sector’s pivotal role in strengthening the digital economy and consolidating pathways toward sustainable growth.